Gambaran Durasi Perawatan Metode Kanguru (PMK) Terhadap Peningkatan Parameter Antropometri Bayi Berat Badan Lahir Rendah (1000-1999 gram) di Rumah Sakit Budi Kemuliaan Tahun 2023: Description of the Duration of Kangaroo Care Method (KMC) on the Improvement of Anthropometric Parameters of Low Birth Weight Babies (1000-1999 grams) at Budi Kemulia Hospital in 2023 - Izona, Donicka; Irma Sapriani; Fitria Endah Puwarni (Indonesian Journal of Midwifery (IJM), 2025)
The Indonesian Ministry of Health in 2021 shows leading causes of neonatal were BBLR at 34.5%, asphyxia at 27.8%, and other causes (congenital abnormalities, infections, neonatal tetanus) 20.2%. The longitudinal research designs use consecutive sampling. Research subjects were 8 infants using the instrument of PMK daily evaluation book at home and a questionnaire. Description of the duration of KMC on the improvement of anthropometric parameters of LBWI (1000-1999 grams) at Budi Kemuliaan Hospital in August-September 2023. Average weight gain for a PMK duration of <10 hours is 24.34 grams/day and duration of ≥10 hours is 28.55 grams/day, length increase for a PMK duration of <10 hours/day is 0.23 cm/week and duration of ≥10 hours/day is 0.46 cm/week, head circumference increase for a PMK duration of <10 hours/day is 0.20 cm/week and duration of ≥10 hours is 0.22 cm/week. Type of breast milk nutrition, weight gain is 28.40 grams/day, height increase is 0.5 cm/week and head circumference increase is 0.2 cm/week. Type of formula milk nutrition, average weight gain is 28.03 grams/day, height increase is 0.5 cm/week and head circumference increase is 0.25 cm/week. Type of breast milk and formula milk nutrition, weight gain is 25.86 grams/day, height increase is 0.30 cm/week and head circumference increase is 0.21 cm/week. An overview of the growth of BBLR with duration of PMK ≥ 10 hours of increased body weight anthropometry, body length and head circumference, for increased anthropometry in nutrients cannot be equalized for increased due to limited research samples. It is hoped that further research can be carried out by expanding the research sample.   Abstrak Kelahiran BBLR masih menjadi pusat perhatian kesehatan di Indonesia. Data Kemenkes RI tahun 2021 proporsi penyebab kematian neonatal (0-28 hari) terbanyak BBLR 34,5%, asfiksia 27,8% dan penyebab lainya (kelainan kongenital, infeksi, tetanus neonatorum) 20,2%. Desain penelitian longitudinal menggunakan consecutive sampling, subjek sebanyak 8 bayi dengan instrumen penelitian buku evaluasi harian PMK dan kuesioner. Studi Kasus durasi Perawatan Metode Kanguru (PMK) terhadap peningkatan parameter antropometri BBLR (1000-1999 gram) di Rumah Sakit Budi Kemuliaan bulan Agustus-September Tahun 2023. Rerata kenaikan berat badan durasi PMK <10 jam 24,34 gram/hari, durasi PMK ≥10 jam 28,55 gram/hari. Rerata kenaikan panjang durasi PMK <10 jam sehari 0,23 cm/minggu, durasi PMK ≥10 jam sehari 0,46 cm/minggu. Rerata kenaikan lingkar kepala dengan durasi PMK<10 jam sehari 0,20 cm/minggu, durasi PMK ≥10 jam 0,22 cm/minggu. Pada jenis nutrisi ASI kenaikan berat badan rerata 28,40 gram,/hari kenaikan panjang badan 0,5 cm/minggu dan kenaikan lingkar kepala 0,2 cm/minggu. Pada jenis nutrisi susu formula rerata kenaikan berat badan 28,03 gram/ hari, panjang badan kenaikan rerata 0,5 cm/minggu dan lingkar kepala rerata 0,25 cm/minggu. Pada jenis nutrisi ASI dan Susu formula kenaikan berat badan rerata 25,86 gram/hari, panjang badan rerata 0,30 cm/minggu dan lingkar kepala rerata kenaikan 0,21 cm/minggu. Gambaran pertumbuhan BBLR dengan durasi PMK ≥10 jam terjadi peningkatan antropometri berat badan, panjang badan dan lingkar kepala, untuk peningkatan antropometri pada nutrisi tidak dapat direratakan untuk peningkatan karena sampel penelitian yang terbatas. Diharapkan penelitian selanjutnya dapat dilakukan kembali dengan memperluas sampel penelitian.